A Near-Infrared Triggered Intracellular pH Regulative PAMAM/O-nitrobenzaldehyde Coated UCNPs for Cancer Therapy. Issue 199 (13th June 2019) - Zhou, Liping; Hu, Hao; Zhang, Yi-Xin; Meng, Qing-Ye; Yu, Bing; Shen, You-Qing; Cong, Hai-Lin
Abstract: Dendrimers have become effective drug carriers and gene transfection vectors for medical biomaterials. In this experiment, UCNPs (NaGdF4 :Tm, Yb@NaGdF4 ) and three-generation PAMAM dendrimers were prepared firstly; then NaGdF4 :Tm, Yb@NaGdF4 was modified by Polyacrylic acid(PAA); PAMAM were grafted to the surface of the modified UCNPs by the reaction between amino groups and carboxyl groups; finally, O-nitrobenzaldehyde was grafted to the surface by Schiff base reaction.The synthesized upconversion materials were coated with PAA and PAMAM, then loaded with O-nitrobenzaldehyde to form spherical nanoparticles. The particle size of prepared nanoparticles is 75 ∼ 80 nm. The dendrimer complex can emit ultraviolet light to regulate the pH gradient of aqueous solution under the excitation of near-infrared light (980 nm), and can be used to kill cancer cells by changing the acidity of tissue cells; secondly, the cavity between dendrimers and dendrimers on the surface of the complex can be used in many fields such as drug delivery and gene transfection; the nanoparticles provide a new method for cancer treatment.